(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article describes the complex structure of human behavior, as well as manifestations of subordinate behavior, the causes of its occurrence and its socio-psychological consequences. The thoughts about how addiction violates the normal life of a person, lifestyle, destroys relationships, destroys the psychological state of oneself and loved ones are highlighted.